Model Penyesuaian Sosial Siswa Baru di Sekolah Menengah Pertama Islam Al-Hamidiyah Depok - Mustika Dewi Muttaqien; Eva Siti Faridah; Ernawati Erawati (Jurnal Dirosah Islamiyah, 2022)
The purpose of this research is to find out level of social adjustment on male and female students, what kind of aspect has high and low level on student social adjustment, and the different of social adjustment based on gender of students. Research was applied in Al-Hamidiyah Islamic Junior High School on August – September 2019 with qualitative approach and survey method to understand phenomena in the field. Student at Seven class are selected as a subject consist of 40 person male and female students. The instrument for collecting data is Likert Scale Questionnaire and data are analyzed through classification, scoring, calculation, comparison and explanation. The result of research are: 1) Student social adjustment in Al-Hamidiyah Islamic Junior High School: individual expression, social affiliation in group, social behavior, and individual satisfaction are good level. 2) There is a same level of student social adjustment both male and female students in high and low. Individual satisfaction in high level and social behavior in low level. It is mean, that the student has individual satisfaction better than their social behavior. 3) There is the different in social adjustment between male and female students. Female students has level better than male students in all aspect of social adjustment. Keyword: Social adjustment, male students, and female students.